Mellemnavnet i Danmark og i Norge - Kællerød, Lars-Jakob Harding (NAMN OG NEMNE, 2019)
This article gives a brief overview of the usage of middle names in Denmark and Norway. The Acts of Personal Names in the Nordic countries, especially the Scandinavian, are in many ways inspired and influenced by each other, but there are also a number of differences. In the 1960s new legislations were introduced in Denmark and Norway caused by similar problems that had occurred. The protected family names were neglected as they were often used as middle names of individuals who did not have a legitimate relation to the name in question. Committees from the three Scandinavian countries collaborated on new legislations where the rules concerning middle names were stricter. Since then, new Acts of Names have been introduced in both Denmark and Norway, and albeit there is clear inspiration from the current Norwegian legislation in the Danish, significant differences are present. In Norway a middle name is a private name and the name-bearer’s children cannot inherit it, while in Denmark that is possible. Furthermore, in Denmark a middle name can be adopted as the individual’s official surname and that is not possible in Norway. The article also gives a short presentation of some selected studies regarding middle names in Norway and Denmark. These studies deal with the usage of middle names in a historical perspective as well as giving some insights in a more modern usage of middle names.